Research on the role of economic and social development agroturism in Romania - Daniela Ileana Godja (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The main purpose of this paper is to present agrotourism, as a "specific phenomenon of the modern world". Agrotourism is circumscribed Romanian society and is influenced by the difficulties facing the Romanian economy, the pace in which the process of economic reform and the emphasis on the tertiary sector and tourism as its constituent part. Romania has an exceptional tourism potential that the attractiveness of the complexity and variety may urge to travel an extremely wide range of tourists, but more importance should be given to transforming this fund tourism in heritage tourism. For the purpose of World Tourism Organization and European organizations of rural tourism, it is a form of tourism which includes any tourist activity organized and managed in rural areas by the local population, exploiting tourism resources local (natural, cultural - historical, human) and facilities, including hostels and tourist structures agrotourism farms. The general objectives of the tourism industry in our country areas should contribute to increasing the number of jobs and income alternatives. Tourism development, even at a smaller scale, holds particular importance as regards the country's economic development and employment.
Keywords: 330; tourism; economic development; heritage tourism